Growth on Formic Acid Is Dependent on Intracellular pH Homeostasis for the Thermoacidophilic Methanotroph Methylacidiphilum sp. RTK17.1 - Carere, Carlo R.; Hards, Kiel; Wigley, Kathryn; Carman, Luke; Houghton, Karen M.; Cook, Gregory M.; Stott, Matthew B. (Frontiers in Microbiology, 2021)
Members of the genus Methylacidiphilum, a clade of metabolically flexible thermoacidophilic methanotrophs from the phylum Verrucomicrobia, can utilize a variety of substrates including methane, methanol, and hydrogen for growth. However, despite sequentially oxidizing methane to carbon dioxide via methanol and formate intermediates, growth on formate as the only source of reducing equivalents (i.e., NADH) has not yet been demonstrated. In many acidophiles, the inability to grow on organic acids has presumed that diffusion of the protonated form (e.g., formic acid) into the cell is accompanied by deprotonation prompting cytosolic acidification, which leads to the denaturation of vital proteins and the collapse of the proton motive force. In this work, we used a combination of biochemical, physiological, chemostat, and transcriptomic approaches to demonstrate that Methylacidiphilum sp. RTK17.1 can utilize formate as a substrate when cells are able to maintain pH homeostasis. Our findings show that Methylacidiphilum sp. RTK17.1 grows optimally with a circumneutral intracellular pH (pH 6.52 ± 0.04) across an extracellular range of pH 1.5–3.0. In batch experiments, formic acid addition resulted in no observable cell growth and cell death due to acidification of the cytosol. Nevertheless, stable growth on formic acid as the only source of energy was demonstrated in continuous chemostat cultures (D = 0.0052 h−1, td = 133 h). During growth on formic acid, biomass yields remained nearly identical to methanol-grown chemostat cultures when normalized per mole electron equivalent. Transcriptome analysis revealed the key genes associated with stress response: methane, methanol, and formate metabolism were differentially expressed in response to growth on formic acid. Collectively, these results show formic acid represents a utilizable source of energy/carbon to the acidophilic methanotrophs within geothermal environments. Findings expand the known metabolic flexibility of verrucomicrobial methanotrophs to include organic acids and provide insight into potential survival strategies used by these species during methane starvation.